Recycling of Dilute Deacetylation Black Liquor to Enable Efficient Recovery and Reuse of Spent Chemicals and Biomass Pretreatment Waste - Chen, Xiaowen; Kuhn, Erik; Nagle, Nick; Nelson, Robert; Tao, Ling; Crawford, Nathan; Tucker, Melvin (Frontiers in Energy Research, 2018)
Deacetylation/dilute alkaline pretreatment followed by mechanical refining (DMR) has been proven as an effective process for biomass sugar liberation without severe chemical modification to lignin. Previous research has been focused on optimizing deacetylation conditions, reducing energy consumptions in mechanical refining, and improving sugar yields and titers in enzymatic hydrolysis. To successfully commercialize this process, another critical challenge is to develop a robust process to balance water usage, recover spent chemicals, and utilize waste carbons from the dilute deacetylation waste liquor. In this work, a new process modification and strategy is pioneered to recycle and reuse the weak black liquor (WBL) in order to reduce water, chemical, and energy usage while increasing both inorganic and organic contents in the WBLto facilitate downstream processing. Results suggest that the accumulation did not lower acetyl and lignin removal in alkaline pretreatment, resulting in comparable sugar yields in enzymatic hydrolysis. Sodium and potassium were found to be the two most important inorganic compounds in the recycled WBL. Moreover, the accumulated sodium and phenolic compounds did not inhibit the downstream ethanol fermentation processes. Finally, techno-economic analysis (TEA) showed a decrease in the minimum ethanol selling price (MESP) by ~5 to 15 cents per gallon of ethanol resulting from the inclusion of the recycling of weak black liquor when compared to a conventional non-recycling process.